Polarization Monitor for High-speed State of Polarization Changes Detection - Dejdar, Petr; Hanák, Pavel; Münster, Petr; Horváth, Tomáš (International Science and Engineering Society, 2021)
The paper describes design of a high-speed polarization monitor system. Describe of hardware design including implementation of FPGA bitstream to the acquisition card and also is presented the graphical user interface (GUI) for processing the measured data. The system is based on Lightwaves2000 Prime controller and a MyRIO device is used for data acquisition. The system is capable sending data from four photodiodes to graphical user interface using the TCP protocol with a sampling frequency of up to 6.5 kS/s. The GUI enables graphical representation of Stokes parameters and also can setup the device parameters. System enables detection of events to an optical fiber caused by changes in ambient conditions using state of polarization (SOP) changes analysis.

The paper describes design of a high-speed polarization monitor system. Describe of hardware design including implementation of FPGA bitstream to the acquisition card and also is presented the graphical user interface (GUI) for processing the measured data. The system is based on Lightwaves2000 Prime controller and a MyRIO device is used for data acquisition. The system is capable sending data from four photodiodes to graphical user interface using the TCP protocol with a sampling frequency of up to 6.5 kS/s. The GUI enables graphical representation of Stokes parameters and also can setup the device parameters. System enables detection of events to an optical fiber caused by changes in ambient conditions using state of polarization (SOP) changes analysis.
Polarization Monitor for High-speed State of Polarization Changes Detection
Keywords: polarization; SOP; sensing; vibration.; polarization; SOP; sensing; vibration.